2018
DOI: 10.12688/wellcomeopenres.14736.1
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the first clinical trial of a non-licensed vaccine among Ugandan adolescents: a phase II field trial of the tuberculosis candidate vaccine, MVA85A

Abstract: Background: A more effective vaccine for tuberculosis (TB) is a global public health priority. Vaccines under development will always need evaluation in endemic settings, most of which have limited resources. Adolescents are an important target population for a new TB vaccine and for other vaccines which are relevant at school-age. However, in most endemic settings there is limited experience of trials of investigational products among adolescents, and adolescents are not routinely vaccinated. Methods: We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Thus, further work should also investigate what incentivises institutions to become a TB vaccine trial centre. For example, prior evaluations of TB vaccine trial centres indicated that difficulties with logistics and operations could pose a problem in terms of trial execution (9,10). Kaguthi et al (11) discuss lessons learned from development of a TB vaccine trial centre for design and implementation of trials in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further work should also investigate what incentivises institutions to become a TB vaccine trial centre. For example, prior evaluations of TB vaccine trial centres indicated that difficulties with logistics and operations could pose a problem in terms of trial execution (9,10). Kaguthi et al (11) discuss lessons learned from development of a TB vaccine trial centre for design and implementation of trials in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was recently shown that infection with S. haematobium induces long-term, persistent epigenetic alterations resulting in a weakened inflammatory response and increased susceptibility to tuberculosis (251). Hence, research on tuberculosis therapies and vaccine candidates has made a point to assess the effect of Schistosoma species on tuberculosis disease progression (252). As both pathogens form granulomas but affect macrophage metabolism in a vastly different manner, it would be interesting to analyze granuloma formation in co-infection settings, particularly with regard to lipid metabolism.…”
Section: Future Perspectivesmentioning
confidence: 99%